(untitled) (Comprehensive Journal of Science, 2025)
The nation of an m-group as algebraic system is relatively new and was intrudes by (Giraudet, M. and Rachunek, J.,1999) when they were studying order properties of monotonic permutation groups of linearly ordered sets. In the present study the containment relationships between the varieties of m-groups will be exhibited where we will prove that the set of all varieties of m-groups are lattice and semigroup. The connections between the varieties of ????m, ????m, ????m, ????m and ????nm will be described.